STRUKTUR DAN KOMPOSISI VEGETASI SEBAGAI PENENTU JASA EKOSISTEM RUANG TERBUKA HIJAU KOTA MARTAPURA SUMATERA SELATAN - , Lia Auliandari; , Bapak Prof. Dr. Ir. Chafid Fandeli, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research was conducted in green open spaces of Martapura City, South Sumatra. The objectives of this research were 1) to study the structure and composition of green space vegetation in offering microclimate regulation service, 2) to study the balance of Martapura green space vegetation community based on the species diversity, and 3) to study the ecosystem services in various forms of green space based on its function. The main method used was a survey. For sampling both the green space areas and the research objects were done using purposive sampling. The research objects were vegetation structure, vegetation composition, microclimate, and respondents' perception. The data were collected by two techniques, namely observation and questionnaires. The observation was used to collect the data of vegetation structure, vegetation composition and microclimate conditions, while the questionnaire was used to study the respondents' perception about green space function. The data obtained from the measurements were analyzed qualitatively. The results showed: 1) the vegetation structure of Martapura City today is a bit species and individuals composing the canopy strata of green space, low species diversity, species evenness high only at certain growth form, and still dominated by a single species, while Martapura vegetation composition is low species richness and rare species density. Those vegetation structure and composition cause the comfort of green space in the morning at three measurement points are in class I (comfortable), while the afternoon and evening are in class II (less comfortable) and class III (uncomfortable). The measurement point under the canopy indicates the comfort with class higher than at outer limit of the canopy and outside the canopy. The increase in comfort needs to be done, especially in the afternoon and evening, 2) based on the value of species diversity in all vegetation growth form is still low, Martapura green spaces havenât shown a balanced state yet, especially on tree vegetation, and 3) based on its function, the existence of the green space can provide ecosystem services such as microclimate regulation service, supporting service (complimentary for habitat or space living animal), cultural services, and provision services. Based on these results, the increase in comfort needs to be done especially in the afternoon and evening with enriching plant species and making high evenness species, especially in tree vegetation, thus increasing the vegetation diversity and density. The high vegetation diversity and density will increase the ability of a community to maintain vegetation remain balanced or steady despite the disruption of its components. Thus, the green space can provide influence maximally, especially in the microclimate regulation.